Assessing the contribution of the Environmental Management Agency (EMA) towards sound wetland management in Harare urban - Tsveta, Trish (2017)
The main objective of the study was to assess the contribution of EMA towards sound wetland management in Harare Urban. Wetlands have been threatened by a number of factors in Harare . It has been established that in the presence of various laws in the management of wetlands in Zimbabwe, wetlands continue to be under threat .Environmental laws have not been adequate in efforts to manage wetlands in Harare Urban. The study targeted the EMA and residents. The researcher has analysed the successes and weaknesses of strategies by EMA aimed towards saving wetlands in Harare Urban. The research recommended that policies which have been put in place to manage wetlands should be harmonised and reviewed to make them effective to avoid wetlands from being threatened by various activities. The laws that manage wetlands in Harare Urban should be enforced by EMA in efforts to contribute to sound wetland management